How can a single rescuer adequately deliver tidal volume with a manual resuscitator? An improved device for delivering regular tidal volume. Issue 1 (3rd December 2010) - Cho, Yong Chul; Cho, Sung Wook; Chung, Sung Pil; Yu, Kweon; Kwon, O Yu; Kim, Seung Whan
Abstract : Objectives: A bag-valve mask (BVM) device is used as one of the first-line pieces of equipment in emergency situations. However, cardiopulmonary support providers do not recognise the exact tidal volume during procedures, and squeezing methods of BVM may not deliver the same tidal volume each time. To supply a regular and sustained tidal volume, adequate finger points were marked on the surface of a BVM. Methods: In this study, a total of 83 volunteers participated and practised conventional BVM and volume-marked bag-valve mask (VBVM) procedures. The VBVM is simply a conventional BVM with an imaginary axis grid, drawn to guide the placement of the fingers. The VBVM method provides a constant volume of approximately 500–600 ml; the bag is squeezed until the thumb and the middle finger touch slightly. The results were then statistically analysed. Results: The tidal volume delivered by the studied VBVM method is more accurate than the conventional BVM method (421.87±95.19 ml vs 534.21±24.22 ml, p<0.001). There was no statistical correlation except age between the results and the participants' training level or physical characteristics in the study. Conclusions: As the conventional BVM method cannot deliver a regular and sustained tidal volume, the authors invented the VBVM method. This method delivered a volume of 500–600 ml with more stability each time, which can improve the outcome of emergency patients.